Preliminary experience of single operative port thoracoscopic anatomical lesion resection for congenital lung malformations in segments S9-10 - Guo, Rui; Zhai, Yunpeng; Zhao, Huashan; Xu, Hongxiu; Shen, Gang; Huang, Sai; Zhang, Shisong (Frontiers in Pediatrics, 2025)
PurposeTo compare the clinical outcomes of single operative port thoracoscopic anatomical lesion resection (TALR) with multi-portal video-assisted thoracic surgery (M-VATS) in the treatment of congenital lung malformations (CLMs) located in pulmonary segments S9-10, and to evaluate its safety and feasibility in routine practice.MethodsWe retrospectively analysed 46 paediatric CLMs cases treated thoracoscopically at our institution from January 2023 to January 2025. Patients were grouped by surgical approach: 13 underwent single operative port TALR, and 33 underwent M-VATS. Clinical parameters were compared between groups.ResultsCompared to M-VATS, the single operative port TALR showed significantly reduced blood loss (P = 0.01), chest tube time (P = 0.04), hospital stays (P = 0.04), and incision length (P < 0.01). No bronchopleural fistulas, conversions to open surgery, no recurrence or residual lesions occurred in either group.Conclusionsingle operative port TALR is safe, feasible, minimally invasive, and offers excellent cosmetic outcomes, representing a promising surgical technique for treating CLMs involving segments S9-10.